Comparative studies about fungal colonization and deoxynivalenol translocation in barley plants inoculated at the base with Fusarium graminearum, Fusarium culmorum and Fusarium pseudograminearum - Pecoraro, F.; Giannini, M.; Beccari, G.; Covarelli, Lorenzo; Filippini, G.; Pisi, A.; Nipoti, P.; Prodi, A. (2018)
Fusarium crown rot (FCR), an important disease of wheat and barley, is mainly caused by Fusarium graminearum, F. culmorum and F. pseudograminearum, which are also responsible for mycotoxin production. This is the first comparative investigation of their colonization on barley plants after stem base inoculation. At plant maturity, FCR symptoms were visually evaluated, fungal biomass was quantified by Real-Time quantitative PCR and deoxynivalenol (DON) was detected by enzyme-linked immunosorbent assay (ELISA). All the inoculated strains caused the typical FCR necrotic symptoms. Real-Time PCR analysis showed that F. graminearum and F. culmorum were present in the head tissues, while F. pseudograminearum colonized only up to the area including the second node of the stem. Conversely, DON was detected up to the head for all the three species. This study shows that, as already demonstrated in previous research for wheat, DON may be detected up to the head as a consequence of stem base infection by the three FCR agents.